Thiocyanate Reduces Motor Impairment in the hMPO-A53T PD Mouse Model While Reducing MPO-Oxidation of Alpha Synuclein in Enlarged LYVE1/AQP4 Positive Periventricular Glymphatic Vessels - Wanda F. Reynolds; Ernst Malle; Richard A. Maki (MDPI AG, 2022)
Parkinson's disease (PD) is due to the oxidation of alpha synuclein (αSyn) contributing to motor impairment. We developed a transgenic mouse model of PD that overexpresses the mutated human αSyn gene (A53T) crossed to a mouse expressing the human MPO gene. This model exhibits increased oxidation and chlorination of αSyn leading to greater motor impairment. In the current study, the hMPO-A53T mice were treated with thiocyanate (SCN−) which is a favored substrate of MPO as compared to chlorine. We show that hMPO-A53T mice treated with SCN− have less chlorination in the brain and show an improvement in motor skills compared to the nontreated hMPO-A53T mice. Interestingly, in the hMPO-A53T mice we found a possible link between MPO-related disease and the glymphatic system which clears waste including αSyn from the brain. The untreated hMPO-A53T mice exhibited an increase in the size of periventricular glymphatic vessels expressing the glymphatic marker LYVE1 and aquaporin 4 (AQP4). These vessels also exhibited an increase in MPO and HOCl-modified epitopes in the glymphatic vessels correlating with loss of ependymal cells lining the ventricles. These findings suggest that MPO may significantly promote the impairment of the glymphatic waste removal system thus contributing to neurodegeneration in PD. Moreover, the inhibition of MPO chlorination/oxidation by SCN− may provide a potential therapeutic approach to this disease.